PENGEMBANGAN MODEL PEMBELAJARAN GERAK DASAR LARI MELALUI PERMAINAN THROW AND RUN PADA SISWA BERKEBUTUHAN KHUSUS (TUNARUNGU) DI SDLB NEGERI SEMARANG TAHUN 2015 (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this research it was produce a model of learning basic movement for kind of run by means thegame Throw and Run on students with special condition (physical defect) in Semarang State SDLB2015.There was product to development procedure includes product analysis to would be created, develop earlyactivities, expert validation and revision, testing and revision of the small group, large group and test the finalproductTest result experts data obtained by the average percentage of the results analysis of the product was76.66% of